Differential tolerance of soybean (Glycine max) to manganese in Mn-deficient soil - BANSAL, R L; NAYYAR, V K (The Indian Journal of Agricultural Sciences, 2013)
An experiment was conducted during rainy season (kharif) of 1989 to study the tolerance of 10 varieties of soybean [Glycine max (L.) Merr.] 10 manganese stress in a Mn-deficient field containing 2.4 mg DTPA-Mn/kg soil. The treatments included the control and 3 foliar sprays of 0.5% manganese sulphate solution. The seed yield of soybean was 86-254 g/2 In row length under Mn-stress condition. Though all the varieties responded to foliar application of Mn. the increase in seed yield varied from 1.0 to 25.0%. The Mn concentration in seeds of different varieties was 10.3-14.3 Î¼g/g and it significantly increased to 13.7-17.5 Î¼g/g with the application of Mn Based on the increase (%) in seed yield on foliar application of Mn, the varieties were grouped least tolerant (,PK 416', 'PK 504' and 'SL 115'), moderately tolerant (,SL 96'. 'SL 110', 'SL 114'. 'Punjab 1' and 'SH 184-25') and tolerant ('SL 133' and 'PK 472').